Epidemiology of Serotype Asia 1 Foot-and-Mouth Disease Virus in China - Perez, Andres Maximiliano (2011)
This manuscript provides insight into the epidemiology of serotype Asia 1 foot-and-mouth disease virus in China. The spatial distribution and temporal dynamics of this serotype, which China reported for the first time after 47 years in 2005, suggests that it may have become endemic in the region.